Teknik Pemingsanan Ikan Bawal Bintang (Trachinotus blochii) menggunakan Ekstrak Daun Senduduk Ungu (Melastoma malabathricum L.): Anesthesia Techniques of Snubnose Pompano (Trachinotus blochii) using Melastoma malabathricum Leaf Extract - R. Marwita Sari Putri; Azwin Apriandi; Tri Yulianto; Facrini Anggianti (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Snubnose pompano (Trachinotus blochii) is one of the commodities of aquaculture featured in Riau Archipelagic Province. This biota has a selling price that is expensive, so that the necessary transport technology innovative to maintain resale value. Melastoma malabathricum leaf is one of the natural ingredients that are suspected of potential to be used as the material of anesthesia. The purpose of this study is to determine the concentration of crude extract the leaves of Melastoma malabathricum according to anesthesia snubnose pompano and survival rate. Baded on the results of the study, the crude extract Melastoma malabathricum best is at a concentration of 25% with the onset time 40.69 minutes and recovered time 13.34 minutes with a survival rate 100%. The quality of the water after anesthesia still in the verge of reasonable limits where the pH value 6.67, dissolved oxygen 4.5, temperature 28.19ºC and total ammoniac nitrogen 1,59 mg/L.